A systematic review of high-risk environmental circumstances for adolescent drinking. (3rd September 2019) - Cox, M. J.; Sewell, K.; Egan, K. L.; Baird, S.; Eby, C.; Ellis, K.; Kuteh, J.
ABSTRACT: Background: The social and physical environment in which drinking occurs can impact the level of alcohol consumption and related consequences among adolescents. Understanding which aspects of the drinking context exert the most risk for adolescent alcohol use is necessary for comprehensive prevention programming. Methods: Following PRISMA guidelines, we systematically reviewed the literature for published studies that examined the relationship between aspects of the social (e.g., number of people present), situational (e.g., adult supervision) and location-based characteristics of the drinking context and adolescent alcohol consumption. A total of 15, 853 articles were screened for inclusion, of which 31 were included for qualitative synthesis. Results: Adolescents most commonly consume alcohol on weekend evenings and either in their home or someone else's home. Availability of alcohol, increased group size, and the presence of others, particularly close friends, who are drinking increases risk for alcohol use. Conclusions: Certain environments exert greater risk for alcohol consumption among adolescents. Characteristics of these high-risk contexts represent modifiable factors of the environment that are informative to prevention and policy efforts. Implications for prevention and future directions are discussed.